High and Dry : Climate Change, Water, and the Economy - World Bank Group (World Bank, Washington, DC, 2016)
The impacts of climate change will be channeled primarily through the water cycle, with consequences that could be large and uneven across the globe. Water-related climate risks cascade through food, energy, urban, and environmental systems. Growing populations, rising incomes, and expanding cities will converge upon a world where the demand for water rises exponentially, while supply becomes more erratic and uncertain. They will jeopardize growth prospects in the regions worst affected and in some of the poorest countries. These challenges are not insurmountable, however, and smart policies that induce water-use efficiency, align incentives across regional and trading partners, and invest in adaptive technologies can go a long way toward reducing or eliminating these negative effects.